ESSENCE AND FEATURES OF CONSULTING IN MODERN EDUCATIONAL ACTIVITIES - Lyudmila М. Skripnik (Alfred Nobel University Publisher, 2021)
In the 21st century in Ukraine, there is a large-scale information transformation in all spheres of life, including education. This is a century of large-scale and radical reforms and changes related to the modernization of state support for education and the emergence of new opportunities for the development of educational services. Now, education is the subject of special research in various fields of knowledge based on ICT. There is a growing number of various ranks employees who have the potential skills of consultants, teachers, coaches, advisors, etc., which in parallel can perform the functions of consultants in educational institutions. Therefore, in the modern world, consultation and consulting become relevant and important. The article considers the concepts of «consulting» and «information consulting»; it reveals the features of pedagogical counselling in modern educational activities. It was found that counselling (consulting) is a specially organized information interaction between the counsellor and those who need help to solve the problem and make positive changes in the activities of an individual or organisation as a whole. The necessity of the development of counselling in the field of education in the period of modernization and cardinal changes in society has been substantiated. The main purpose of consulting activities at educational institutions has been elucidated, which involves the dissemination and implementation in this process modern advances in science and technology, providing students and population with advisory services on the use of modern technologies and social development, giving consultations and support for various projects, raising the knowledge level and improving the practical skills of those involved in pedagogical interaction. The specifics, functions (consulting, scientific, research, mediation, training ones), role and main directions of development of consulting activity in educational institutions have been determined. Two primary areas that require the systematic use of consulting services in educational institutions have been analyzed, among them the methodological and career counselling. Pedagogical, socio-pedagogical, psychological and managerial types of educational consulting and related with them the informational, career guidance and reputation types of consulting have been characterized. Promising technologies that can provide full-fledged consulting services have been outlined. They cover computer-based pedagogical technologies and the ones that ensure the proper interaction of participants in the educational process. The difficulties and contradictions inherent in the stage of formation of the information and consulting environment of educational institution and the development of consulting services in the field of education have been considered.